Arbitration as an alternative to judicial dispute resolution, when and why? - ذياب , آلاء; غسان علي , (Latakia University Journal - Economic and Legal Sciences Series, 2022)
Arbitration is a legal, consensual method for settling disputes instead of the judiciary and performs the same function that the judiciary performs with a decisive decision to the dispute, and it must be implemented by the public authority and in the same department competent to implement judicial rulings. Where arbitration plays an important role as a mechanism for settling disputes, whether at the level of international relations or at the level of national relations, even if individuals resort to arbitration as an alternative to the internal judiciary is the source of the advantages achieved by this private judiciary. This study aims to clarify the nature of arbitration, its definition and types, its role in settling disputes, the relationship between arbitration and the judiciary, and the reasons for resorting to arbitration by highlighting the advantages and characteristics of arbitration, the relationship of arbitration with the judiciary, and a review of some Syrian legal texts in this field. The study concluded that arbitration represents a special judiciary, according to which disputes may be robbed from the national judiciary, to be decided by specific persons or arbitral institutions entrusted with the exercise of a special judicial function, and that one of the most important features of the arbitration system that pushes the disputants or contractors to resort to arbitration in the settlement of Disputes as an alternative to the judiciary are confidentiality, flexibility and speed of procedures. In Syrian law, it is not permissible to agree on arbitration in matters in which reconciliation is not permissible, or in violation of public order, or related to nationality or personal status, and arbitration may be resorted to in mainly commercial matters and non-violating civil matters. for the general system.